(untitled) (Annals of Medical Research, 2021)
Aim: Hemodialysis patients should have an access to a vessel. Thrombosis is responsible for 80-85% of fistula losses. Mean Platelet Volume (MPV) is routinely measured in complete blood count and shows the average volume of circulating platelets. In our study, we aimed to investigate whether MPV values may be used as a cheap and noninvasive marker in the early diagnosis and intervention of arteriovenous fistula (AVF) thrombosis.Material and Methods: This retrospective study included 48 patients having one or more episodes of late fistula thrombosis at the hemodialysis unit and 47 patients without history of AVF thrombosis.Results: Demographic and laboratory characteristics were used to compare between groups and no significant difference was found (p> 0.05). On the other hand, significant difference was reported (p=0.001) by the comparison of two groups. Logistic regression analysis, revealed that MPV was an independent risk predictor for the development of AVF thrombosis (p 0.05).Conclusion: AVF dysfunction leads to a significant cost and frequent hospitalization of the patient. Previously, MPV was stated to be a risk factor for arterial and venous thrombosis. This study showed that MPV values may be used in hemodialysis patients as a predictor of thrombosis. Further prospective and retrospective studies should be conducted in order to verify the finding of this study.